Bacterial NanoCellulose: what future? - Gama, F. M. (2018)
Acetic acid bacteria (AAB) have been used in various fermentation processes. Of several ABB, the bacterial nanocellulose (BNC) producers, notably Komagataeibacter xylinus, appears as an interesting species, in large part because of their ability in the secretion of cellulose as nano/microfibrils. In fact, BNC is characterized by a native nanofibrillar structure, which may outperform the currently used celluloses in the food industry as a promising novel hydrocolloid additive. During the last couple of years, a number of companies worldwide have introduced some BNC-based products to the market. The main aim of this editorial is to underline the BNC potentials.